2022
DOI: 10.1038/s41564-022-01261-2
|View full text |Cite
|
Sign up to set email alerts
|

PCRCR complex is essential for invasion of human erythrocytes by Plasmodium falciparum

Abstract: The most severe form of malaria is caused by Plasmodium falciparum. These parasites invade human erythrocytes, and an essential step in this process involves the ligand PfRh5, which forms a complex with cysteine-rich protective antigen (CyRPA) and PfRh5-interacting protein (PfRipr) (RCR complex) and binds basigin on the host cell. We identified a heteromeric disulfide-linked complex consisting of P. falciparum Plasmodium thrombospondin-related apical merozoite protein (PfPTRAMP) and P. falciparum cysteine-rich… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
73
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2
1

Relationship

1
5

Authors

Journals

citations
Cited by 44 publications
(76 citation statements)
references
References 57 publications
3
73
0
Order By: Relevance
“…To determine if Rh5 proc and Rh5 unproc were able to bind to basigin on the surface of human erythrocytes, we used uorescence-activated cell sorting (FACS) and detected binding using anti-PfRh5 antibodies. This showed that Rh5 proc bound to human erythrocytes at levels like that described previously 23,30 , however, the full-length Rh5 unproc did not show any apparent binding (Fig. 5c).…”
Section: Resultssupporting
confidence: 73%
See 4 more Smart Citations
“…To determine if Rh5 proc and Rh5 unproc were able to bind to basigin on the surface of human erythrocytes, we used uorescence-activated cell sorting (FACS) and detected binding using anti-PfRh5 antibodies. This showed that Rh5 proc bound to human erythrocytes at levels like that described previously 23,30 , however, the full-length Rh5 unproc did not show any apparent binding (Fig. 5c).…”
Section: Resultssupporting
confidence: 73%
“…Additionally, the ability of Rh5 proc and Rh5 unproc to participate in formation of the PCRCR complex was compared by rstly, testing their ability to bind the preformed PfRipr-CyRPA complex. Both proteins bound to PfRipr-CyRPA equally well and secondly, to the cysteine-linked PTRAMP-CSS hetero-dimer 23 . These showed that both Rh5 proc and Rh5 unproc were able to form the PCRCR complex equally well consistent with their normal function.…”
Section: Resultsmentioning
confidence: 95%
See 3 more Smart Citations